Contrast-induced nephropathy in patients undergoing primary angioplasty for acute myocardial infarction: incidence, a simple risk score, and prognosis - Uyarel, Huseyin; Cam, Nese; Ergelen, Mehmet; Akkaya, Emre; Ayhan, Erkan; Isik, Turgay; Cicek, Gokhan; Gunaydin, Zeki Yuksel; Osmonov, Damirbek; Gul, Mehmet; Demirci, Deniz; Guney, Mehmet Rasit; et al. (Archives of Medical Science, 2009)
Introduction: Patients undergoing primary angioplasty for ST-segment elevation myocardial infarction (STEMI) may be at increased risk of contrast-induced nephropathy (CIN) because of inadequate prophylaxis. We investigated the incidence, predictive factors, and outcomes of CIN after primary percutaneous coronary intervention (PCI). Material and methods: 2521 consecutive STEMI patients (mean age 56.5 ±11.8, years, 2091 male, baseline creatinine 0.97 ±0.3 mg/dl) undergoing primary PCI were retrospectively enrolled in the present study. Results: Contrast-induced nephropathy was defined as an increase in serum creatinine level ł 0.5 mg/dl or ł 25% from baseline within 72 h of radiocontrast administration. 630 patients (25%) developed CIN. Patients with baseline creatinine > 1.5 mg/dl developed CIN more often than those with creatinine Ł 1.5 mg/dl (45.9 vs. 24%, p 250 ml (OR 1.34, 95% CI 1.01-1.78, p = 0.04), age ł 75 years (OR 2.07, 95% CI 1.36-3.12, p = 0.001), anterior infarction (OR 1.26, 95% CI 0.99-1.60, p = 0.05). Higher in-hospital mortality rate was observed in patients developing CIN (9.5 and 1.2%, p < 0.001). Cox regression analysis showed that CIN was a predictor of long-term cardiovascular mortality (hazard ratio [HR] 1.90, 95% CI 1.16-3.12, p = 0.01) and major cardiovascular events (HR 1.34, 95% CI 1.04-1.72, p = 0.025). Conclusions: Contrast-induced nephropathy in patients with STEMI undergoing primary PCI is associated with a markedly increased risk of major cardiovascular events as well as in-hospital and long-term mortality.